Politeness Strategies Of The Characters In Becoming Jane Movie Script By Kevin Hood And Sarah Willimas - Imran, La Ode; Moelier, Dahlia D.; Asyrafunnisa, Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2023)
Humans cannot survive alone if others are not present. Interaction as achieved through contact and communication as a social creature. Humans practically communicate with one another through the use of language. Language has an important part in human communication since it serves as a media tool for engagement. When a language is employed, something about the relationship among the individuals is exposed. This research aimed to explored the used of politeness strategies in Becoming Jane Movie Script and how the characters used politeness strategies in their utterance. The researcher used qualitative technique to explain more the types of politeness strategies and describe how the characters use politeness strategies in Becoming Jane movie Script. The data were analyzed applying politeness strategies theory by Brown and Levinson (1987, p. 68). The researcher found that there were two types of politeness strategies in Becoming Jane movie script namely Bald-on Record and Positive Politeness. The researcher also found how the characters used politeness strategies in their utterance which as the influenced factors were pay-off, relevant circumstances; power (P) and Social Distance (D)